2017
DOI: 10.1371/journal.pone.0180387
|View full text |Cite
|
Sign up to set email alerts
|

Renal osteodystrophy in the obesity era: Is metabolic syndrome relevant?

Abstract: BackgroundObservational studies have shown a beneficial effect of obesity on bone health; however, most of those studies were not based on bone biopsies. Metabolic syndrome (MetS) could have an effect on bone remodeling. However, there are no data on the effects of MetS in the presence of renal osteodystrophy.ObjectiveThe aim of this study was to investigate associations between MetS and renal osteodystrophy using the bone histomorphometric turnover-mineralization-volume (TMV) classification.Design, setting, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…High levels of Pi are prone to impaired metabolism of Ca and Pi, which affects Ca absorption and thus is detrimental to bone health. 34,35 In HFD mice, which usually have reduced Ca and elevated Pi levels, dietary intervention with SC significantly mitigated the increase in Pi levels and elevated bone Ca content and serum Ca levels. Some research studies have suggested that fatty acids can influence the secretion and activity of parathyroid hormone (PTH), a key regulator of calcium and phosphorus levels in the blood.…”
Section: Food and Function Papermentioning
confidence: 99%
“…High levels of Pi are prone to impaired metabolism of Ca and Pi, which affects Ca absorption and thus is detrimental to bone health. 34,35 In HFD mice, which usually have reduced Ca and elevated Pi levels, dietary intervention with SC significantly mitigated the increase in Pi levels and elevated bone Ca content and serum Ca levels. Some research studies have suggested that fatty acids can influence the secretion and activity of parathyroid hormone (PTH), a key regulator of calcium and phosphorus levels in the blood.…”
Section: Food and Function Papermentioning
confidence: 99%
“…In addition to promoting direct kidney damage, high caloric intake also affects renal disease indirectly (through the development of obesity and type 2 diabetes). Obesity may influence the progression of chronic kidney disease (CKD) due to its effects on renal hemodynamics that result in hyperfiltration, increased caloric intake and reduced caloric intake may promote bone disorders [24][25][26][27], although their influence on CKD-MBD has not been sufficiently explored [28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, changes in mineral metabolism are often accompanied by bone disease [ 23 ]. Emerging data indicate that both excessive caloric intake and reduced caloric intake may promote bone disorders [ 24 , 25 , 26 , 27 ], although their influence on CKD-MBD has not been sufficiently explored [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…All of these CKD-associated derangements are collectively known as metabolic bone disease (MBD) [12]. Emerging evidence indicates that excessive caloric intake and obesity are also likely to promote bone disorders [13,14], although their influence on CKD-MDB is unclear [15].…”
Section: Introductionmentioning
confidence: 99%